Seeking Asylum in Japan: Oral Tales of a Contemporary Other - Orikasa, Minami (eCahiers de l'Institut, 2023)
This ePaper is a historically informed analysis of the experiences of asylum seekers in Japan. It engages in ethnographic research through the first-hand accounts of 37 asylum seekers, adapted from interviews conducted by Sophia University's Refugee Voices Japan project. The perceptions, policies, and practices related to asylum seekers are products of the systemic invisibilisation of mobility and migrants' roles throughout Japanese history, despite their highly politicised presence in mainstream discourses. The ePaper addresses the continued absence of knowledge about asylum seekers by centralising their voices and stories, which opens a window into the complex realities of their experiences of displacement and seeking asylum in Japan. Their narratives demonstrate that the immigration regime severely restricts all aspects of their lives. Yet, asylum seekers are not passive victims 'stuck in limbo' but are active members of society employing various strategies in search of solutions for a less precarious life. We extend our heartfelt thanks to the Vahabzadeh Foundation for financially supporting the publication of best works by young researchers of the Graduate Institute, giving a priority to those who have been awarded academic prizes for their master's dissertations.